Tyrosine Aminotransferase Contributes to Benzylisoquinoline Alkaloid Biosynthesis in Opium Poppy(1)([W]) - Lee, Eun-Jeong (American Society of Plant Biologists, 2011)
Tyrosine aminotransferase (TyrAT) catalyzes the transamination of l-Tyr and α-ketoglutarate, yielding 4-hydroxyphenylpyruvic acid and l-glutamate. The decarboxylation product of 4-hydroxyphenylpyruvic acid, 4-hydroxyphenylacetaldehyde, is a precursor to a large and diverse group of natural products known collectively as benzylisoquinoline alkaloids (BIAs). We have isolated and characterized a TyrAT cDNA from opium poppy (Papaver somniferum), which remains the only commercial source for several pharmaceutical BIAs, including codeine, morphine, and noscapine. TyrAT belongs to group I pyridoxal 5′-phosphate (PLP)-dependent enzymes wherein Schiff base formation occurs between PLP and a specific Lys residue. The amino acid sequence of TyrAT showed considerable homology to other putative plant TyrATs, although few of these have been functionally characterized. Purified, recombinant TyrAT displayed a molecular mass of approximately 46 kD and a substrate preference for l-Tyr and α-ketoglutarate, with apparent K(m) values of 1.82 and 0.35 mm, respectively. No specific requirement for PLP was detected in vitro. Liquid chromatography-tandem mass spectrometry confirmed the conversion of l-Tyr to 4-hydroxyphenylpyruvate. TyrAT gene transcripts were most abundant in roots and stems of mature opium poppy plants. Virus-induced gene silencing was used to evaluate the contribution of TyrAT to BIA metabolism in opium poppy. TyrAT transcript levels were reduced by at least 80% in silenced plants compared with controls and showed a moderate reduction in total alkaloid content. The modest correlation between transcript levels and BIA accumulation in opium poppy supports a role for TyrAT in the generation of alkaloid precursors, but it also suggests the occurrence of other sources for 4-hydroxyphenylacetaldehyde.